The Church of the Holy Cross of Ałt'amar : politics, art, spirituality in the Kingdom of Vaspurakan - Pogossian, Zaroui; Vardanyan, Edda (Armenian texts and studies,, 2019)
"This book is dedicated to an outstanding architectural monument of medieval Armenia - the church of the Holy Cross, built in the tenth century on the island of Ałt'amar on Lake Van, and a UNESCO world heritage site. This jewel of architecture has been researched mainly from an art historical perspective. The current multi-author volume offers diverse studies aimed at placing the construction of the church in its proper historical, political, religious, and spiritual context. It explores the intellectual climate in the Kingdom of Vaspurakan during the reign of its founder, King Gagik Arcruni, the Kingdom's relations with Byzantium and the Abbasids, analyzes local historiography, biblical exegesis, hagiography, veneration of the True Cross, and royal ideology. Novel interpretations of architectural features and sculptural decorations close the volume. Contributors are Krikor Bélédian, Jean-Claude Cheynet, Patrick Donabédian, Bernard Flusin, Tim Greenwood, Gohar Grigoryan, Armen Kazaryan, Davit Kertmenjyan, Sergio La Porta, Jean-Pierre Mahé, Zaroui Pogossian, Robert Thomson ([daggar]), Alison Vacca, Edda Vardanyan"--